Application of Ash-Shafi'i Method in Learning Tahsin Al Qur'an in Mushallah Ahsanul Qolbu : Penerapan metode Asy-Syafi'i Dalam Pembelajaran Tahsin Al Qur’an Di Mushallah Ahsanul Qolbu - Mappanyompa; Hidayatussaliki (Halaqa: Islamic Education Journal, 2021)
The purpose of this research is: Analyzing and describing the impact of the application of ash-Shafi'i method in the learning of Tahsin Al-Quran in Mushallah Ahsanul Qolbu Housing Griya Sehati Terongtawah by making students more independent, more active and not boring in the learning process, the methods given in this book use the pattern of self-reliance and continuous exercises. The type of research that the authors conducted is field research directly from the research site using observations, interviews, and documentation which is then analyzed using interactive analysis techniques of Model Miles and Huberman which include data reduction, presenting data, to verifying and concluding data. The results of this study is the application of ash-Shafi'i method conducted by teachers in the learning of the Qur‟an has a good impact on the ability to read the Qur'an‟an learners, learning planning, and evaluation of learning is inseparable from the standard provisions of the method of Ash-Shafi'i namely opening, apersepsi, planting concepts, understanding concepts, exercises / skills independence, evaluation and closing.